Progressive transformation of the HIV-1 reservoir cell profile over two decades of antiviral therapy - Lian, Xiaodong; Seiger, Kyra W.; Parsons, Elizabeth M.; Gao, Ce; Sun, Weiwei; Gladkov, Gregory T.; Roseto, Isabelle C.; Einkauf, Kevin B.; Osborn, Matthew R.; Chevalier, Joshua M.; Jiang, Chenyang; Blackmer, Jane; et al. (Cell host & microbe, 2023)
HIV-1 establishes a life-long reservoir of virally infected cells which cannot be eliminated by antiretroviral therapy (ART). Here, we demonstrate a markedly altered viral reservoir profile of long-term ART-treated individuals, characterized by large clones of intact proviruses preferentially integrated in heterochromatin locations, most prominently in centromeric satellite/micro-satellite DNA. Longitudinal evaluations suggested that this specific reservoir configuration results from selection processes that promote the persistence of intact proviruses in repressive chromatin positions, while proviruses in permissive chromosomal locations are more likely to be eliminated. A bias toward chromosomal integration sites in heterochromatin locations was also observed for intact proviruses in study participants who maintained viral control after discontinuation of antiretroviral therapy. Together, these results raise the possibility that antiviral selection mechanisms during long-term ART may induce an HIV-1 reservoir structure with features of deep latency and, possibly, more limited abilities to drive rebound viremia upon treatment interruptions. [Display omitted] •After LT-ART, intact HIV proviruses are predominantly integrated in heterochromatin•These distinct integration sites result from longitudinal selection mechanisms•No similar selection processes are observed for defective proviruses•Intact proviruses are mainly integrated in heterochromatin in post-treatment controllers Lian et al. show that following two decades of continuous antiretroviral therapy, the integration site profile of intact HIV-1 proviruses is heavily biased toward heterochromatin locations, likely as a result of immune selection mechanisms; such proviruses are less transcriptionally active and, possibly, less rebound competent.